Acute melatonin administration enhances aerobic tolerance: an analysis of biochemical and hematological parameters - Wladimir Rafael Beck; Leonardo Henrique Dalcheco Messias; Franciele Carneiro da Silva; Fúlvia Barros Manchado-Gobatto; Claudio Alexandre Gobatto (Motriz: Revista de Educacao Fisica, 2018)
Abstract Aims This study is aimed at testing the acute melatonin administration (oral; 6 mg) on aerobic tolerance at cycloergometer and analyzing the consequences on biochemical and hematological parameters. Methods The maximal aerobic capacity intensity (iMAC) at cycloergometer of eleven male healthy men (24.18±3.92 years-old; 87.07±12.48 kg; 1.82±0.05 m; 26.18±3.63 kg/m2; and 16.28±5.77 % of fat) was individually determined and used to perform a time to exhaustion (tlim) trial of 30 minutes after melatonin or placebo administration. We observed 48-72h interval between tests, performed in a double-blind experiment design. In order to determine hematological and biochemical parameters we collected venous blood samples before and after tlim. Statistical significance was set at 5%. Results The intensity and the lactatemia corresponding to the maximal aerobic capacity were 120.88±18.78 W and 3.32±1.03 mmol.L-1, respectively. The tlim with placebo (33.94±15.26 min, confidence interval = 24.92 - 42.95) was significantly lower than the tlim with melatonin (41.94±17.22 min; CI = 31.76 - 52.12; p = 0.03; 19.06%; effect size = 0.49). All of the 21 analyzed blood physiological variables resulted in no significant variation after tlim when placebo was compared to melatonin, except for total sera cholesterol (lower after exercise with melatonin). Conclusion Acute melatonin administration enhanced aerobic tolerance at iMAC in 19% at cycloergometer; however, the biochemical and hematological variables assessed were not significantly modulated.